Pharmacokinetic evaluation of lamivudine and zidovudine tablets in human plasma (Revista Brasileira de Ciências Farmacêuticas, 2004)
The purpose of this work was an evaluation of the pharmacokinetic profile from lamivudine and zidovudine combination tablets, produced by Laboratório Farmacêutico do Estado de Pernambuco - LAFEPE. The formulation was administered in 10 volunteers and the concentration-time serum profile was observed from both antiretroviral agents during 12 hours. From concentration-time serum profile the pharmacokinetic parameters for both drugs were calculated by statistical methods. The results were compared with those from experiments carried out by other authors referred in this paper. Differences between the results obtained herein and those from other authors were not significant. The kinetic profile for both substances was not modified by the anti-retroviral combination.